Munasabah Al-Qur’an Perspektif Pendidikan Islam - Afifah, Qorina Khoirul (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2025)
Knowledge of the Qur'an also known as "Ulumul Qur'an" arises as a result of a Muslim's contact with it, either by reading or studying it. The science known as Ulumul Qur'an studies all things related to the Qur'an. 'A. In 'Ulumul Qur'an, there are several branches that will continue to develop as long as the Qur'an is studied. Munasabah Al-Qur'an is one of the branches of 'Ulumul Qur'an. This essay is written using a literary study approach with the intention of revealing everything about the munasabah of the Qur'an from the point of view of Islamic Education in Indonesia. In order to understand the Qur'an as a whole and holistically (holistically), one of the ulumul al-Qur'an known as munasabah explains how the elements of the Qur'an are interconnected or integrated. The goals and curricula of Islamic education in Indonesia show how important the munasabah of the Qur'an is for the practice of Islam in that country